2022
DOI: 10.1007/s13132-022-00984-1
|View full text |Cite
|
Sign up to set email alerts
|

Design Thinking Innovation Within the Quadruple Helix Approach: a Proposed Framework to Enhance Student Engagement Through Active Learning in Digital Marketing Pedagogy

Abstract: The purpose of this paper is to develop a framework for enhancing student engagement through active learning and design thinking workshops online. The COVID-19 pandemic has increased the need for digital engagement exponentially, yet the important experiences of collaborative and active learning (AL) have become more challenging to facilitate and support in circumstances of remote access during classes. As such, design thinking (DT) online presented a unique opportunity to explore this collaborative approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Such involvement is also applicable to other institutions with similar attributes. This argument is supported by Bustard et al (2022), who found that such collaborative efforts create new value in digital pedagogies. Students' remote learning outcomes are relatively affected by the various university support services for remote learning, students' experience in online exams or tests, and their self-motivation in remote learning.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Such involvement is also applicable to other institutions with similar attributes. This argument is supported by Bustard et al (2022), who found that such collaborative efforts create new value in digital pedagogies. Students' remote learning outcomes are relatively affected by the various university support services for remote learning, students' experience in online exams or tests, and their self-motivation in remote learning.…”
Section: Discussionmentioning
confidence: 92%
“…As a result, remote learning during the pandemic significantly affects students' educational experiences, well-being, mental health, and financial aspects (Houlden & Veletsianos, 2022). Furthermore, the above concerns can further be improved by integrating Quadruple Helix Model elements such as partners, co-creators, and other stakeholders, facilitating design innovation toward co-creating new value in online marketing pedagogies and curriculum design, adding values in higher education during the COVID-19 pandemic (Bustard et al, 2022). Thus, it is essential for UCN to create virtual interactions between its students with their Indigenous communities and virtual Indigenous cultural activities while offering remote teaching.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, remote learning during the pandemic signi cantly affects students' educational experiences, well-being, mental health, and nancial aspects (Houlden & Veletsianos, 2022). Furthermore, the above concerns can further be improved by integrating Quadruple Helix Model elements such as partners, co-creators, and other stakeholders, facilitating design innovation toward co-creating new value in online marketing pedagogies and curriculum design, adding values in higher education during the COVID-19 pandemic (Bustard et al, 2022). Thus, it is essential for UCN to create virtual interactions between its students with their Indigenous communities and virtual Indigenous cultural activities while offering remote teaching.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important ways to promote sustainable development is to use design thinking to build knowledge, know-how, and innovative activities. All actors must collaborate within the framework of the Quintuple HM in order to create knowledge societies through design thinking Bustard et al, 2022).…”
Section: Conclusion Limitations and Recommendationmentioning
confidence: 99%